Teach the Child and Not the Subject Alone: Building Entrepreneurial Competencies in Teachers to Meet the Challenges of the 4th Industrial Revolution - Rao, Sarojini (Digital Repository of Theses, 2024)
The purpose of education is to prepare students for a life which is getting increasingly uncertain and ambiguous. They will also have to co-exist in a highly technology driven environment. Information is getting outdated every day and AI has taken over most cognitive skills. The readiness for this starts with the teacher. The whole concept of teach the child and not the subject alone emanates from here. The mantra is Human Intelligence + Artificial Intelligence = Innovative Intelligence. It is a collaborative effort.